Bacteriological profile and antibiotic susceptibility pattern in neonatal sepsis in a tertiary care hospital - Rajkumar khati,Dr.Harshada Shah,Dr.Chaudhary Devendra (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Neonatal sepsis is a significant cause of morbidity and mortality worldwide,yet there is no clear consensus definition, with positive blood cultures serving as thegold standard for diagnosis. Diagnosing sepsis in neonates is challenging due tovarying definitions of “culture negative” or “suspected” sepsis.